Evolution of development of territorial planning of land use in Ukraine - Dorosh, O. S. (Землеустрій, кадастр і моніторинг земель, 2012)
The necessity of restoring Institute of territorisl development planning of land use in Ukraine in time of function of the state, municipal and private lsnd ownership is proved.